An Integrated Population Pharmacokinetic Analysis to Characterize Levonorgestrel Pharmacokinetics After Different Administration Routes. (12th September 2018) - Reinecke, Isabel; Hofmann, Birte; Mesic, Emir; Drenth, Henk‐Jan; Garmann, Dirk
Abstract: To compare the pharmacokinetics (PK) of the progestin levonorgestrel for various routes of administration, an integrated population PK analysis was performed. This analysis integrated data from 10 clinical pharmacology studies and resulted in a single, comprehensive population PK model (and its applications) describing the PK of levonorgestrel and its variability for 6 levonorgestrel‐containing contraceptives: 3 intrauterine systems (IUSs; levonorgestrel [LNG]‐IUS 20 [Mirena ® ], LNG‐IUS 12 [Kyleena ® ], and LNG‐IUS 8 [Jaydess ® /Skyla ® ]); 2 oral contraceptives (the progestin‐only pill [Microlut ® /Norgeston ® ] and the combined oral contraceptive [Miranova ® ]); and a subdermal implant (Jadelle ® ). The levonorgestrel‐containing contraceptives administered orally or as an implant act mainly via their systemic (unbound) levonorgestrel exposure, whereas levonorgestrel administered via an IUS is released directly into the uterine cavity, resulting in lower systemic levonorgestrel concentrations. The integrated population PK analysis revealed that the combined oral contraceptive led to the highest levonorgestrel exposure, followed by the progestin‐only pill and the implant, which led to similar levonorgestrel exposure, and the IUSs, which led to the lowest levonorgestrel exposure (in decreasing order: LNG‐IUS 20, LNG‐IUS 12, and LNG‐IUS 8). The difference was even more distinct at the end of the indicated duration of use of 3 years (LNG‐IUS 8) and 5 years (LNG‐IUS 20 and LNG‐IUS 12). Comparing the 3 IUSs and the implant, in vivo release rates were highest for the implant, followed by LNG‐IUS 20, then LNG‐IUS 12, and were lowest for LNG‐IUS 8. This is in line with the comparison of the total levonorgestrel concentrations.